Efektivitas Kaizenesia dalam Peningkatan Budaya Keselamatan Pasien di Rumah Sakit - Mardahlia, Dewi; Dzakwan, M. Sabiq; Nurhasanah, Nurhasanah (Bunda Edu-Midwifery Journal (BEMJ), 2025)
The concept of Kaizen was a philosophy aimed at improving productivity, efficiency, quality, and customer satisfaction by continuously improving existing work processes, systems, and practices. Data showed that patient safety incidents occurred in 2.9% of inpatients, and 6.6% of those patients died. In fact, 53% of the total incidents were preventable. Other research stated that 58% of patient safety incidents were actually preventable. Globally, 4 out of 10 patients experienced harmful incidents in primary and outpatient care. In fact, 80% of patient safety incidents were actually preventable. One of the efforts in preventing patient safety incidents was the implementation of the Kaizen concept. The aim of the research was to analyze the effectiveness of Kaizenesia in improving the patient safety culture in hospitals. This study used a quasi-experimental method with a pretest-posttest control group design involving 34 respondents as the sample. The results of the study showed differences in the average scores of the patient safety culture before and after the intervention. The p-value of the patient safety culture was 0.001, while for the book, it was 0.127. Based on the mean value, the intervention of applying Kaizenesia was effective in improving the patient safety culture among nurses in the hospital.